2017
DOI: 10.5194/isprs-archives-xlii-2-w3-425-2017
|View full text |Cite
|
Sign up to set email alerts
|

3d Modelling and Mapping for Virtual Exploration of Underwater Archaeology Assets

Abstract: This paper investigates immersive technologies to increase exploration time in an underwater archaeological site, both for the public, as well as, for researchers and scholars. Focus is on the Mazotos shipwreck site in Cyprus, which is located 44 meters underwater. The aim of this work is two-fold: (a) realistic modelling and mapping of the site and (b) an immersive virtual reality visit. For 3D modelling and mapping optical data were used. The underwater exploration is composed of a variety of sea elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Stereo systems have been used for numerous underwater applications such as robotic control (Sagara et al, 2013), archeology (Liarokapis et al, 2017), and surveying (Williams et al, 2016). These systems consist of two horizontally displaced cameras that simultaneously photograph a scene from slightly different perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereo systems have been used for numerous underwater applications such as robotic control (Sagara et al, 2013), archeology (Liarokapis et al, 2017), and surveying (Williams et al, 2016). These systems consist of two horizontally displaced cameras that simultaneously photograph a scene from slightly different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the performance of the PMVSbased stereo-matching technique declines markedly in high turbidity conditions. Liarokapis et al (2017) used PhotoScan R (Agisoft, St. Petersburg, Russia), a state-of-the-art commercially available software package, for 3D modeling and mapping of underwater archaeology sites. Agisoft's PhotoScan R handles all stages of the 3D reconstruction pipeline, including the dense multiview stereo-matching stage.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising and popular technologies that provides the user with an integration of digital contents with real images is augmented reality (AR) (Vecchio et al, 2015). Unlike land sites, semi (/or fully) submerged settlements, ancient ports, shipwrecks and coastal instatements are not accessible to public due to their special (sub) marine environment and depth (Liarokapis et al, 2017). Through the remarkable achievements in digital technologies, including wireless communications and smart devices, the exploitation of AR models is now feasible, in order to provide a better understanding of coastal and underwater cultural heritage assets.…”
Section: Introductionmentioning
confidence: 99%
“…Among the digital technologies, Virtual Reality (VR) has proven its effectiveness in increasing the value of cultural heritage and in the last years it has been efficiently applied for the visualization and exploitation of the UCH (Chapman et al, 2006;Liarokapis et al, 2017;Bruno et al, 2016Bruno et al, , 2018. In fact, VR technology can be efficiently applied to this field in order to make underwater archaeological sites the most accessible to the general public without any constraint given by distance, depth or time.…”
Section: Introductionmentioning
confidence: 99%